National Socialist extermination policies : contemporary German perspectives and controversies - Herbert, Ulrich 1951- (Studies on war and Genocide, 2000)
Extermination policy : new answers and questions about the history of the "Holocaust" in German historiography / Ulrich Herbert -- "Jewish resettlement" : reflections on the political prehistory of the Holocaust / G(c)œtz Aly -- The murder of Jews in the general government / Dieter Pohl -- Anti-Jewish policy and the murder of the Jews in the District of Galicia, 1941/42 / Thomas Sandk(c)ơhler -- The German military command in Paris and the deportation of the French Jews / Ulrich Herbert -- The extermination of the Jews in Serbia / Walter Manoschek -- The National Socialist "solution of the Gypsy question" / Michael Zimmermann -- German economic interests, occupation policy, and the murder of the Jews in Belorussia, 1941/43 / Christian Gerlach -- The war and the killing of the Lithuanian Jews / Christoph Dieckmann -- In the shadow of Auschwitz : the murder of the Jews of East Upper Silesia / Sybille Steinbacher -- The concentration camp SS as a functional elite / Karin Orth